HIGH-QUALITY EMPLOYMENT INDEX CONSTRUCTION BY SECOND CLASSROOM EMPOWERMENT: Based On Survey Data From Zhanjiang University Of Science And Technology - Yang, Xiaojuan; Xie, Qinghua (International Journal of Business, Law, and Education, 2022)
The transfer of independent colleges has intensified the competition for talent training among ordinary colleges and universities. The "invisible hand" guides the transformation of independent colleges from basic survival to conscious, high-quality development. According to the three shifts from survival to a successful transformation of high-quality development, from extensive expansion to exemplary management, from improving the initial employment rate of students to High-quality Employment（HQE） of graduates of Zhanjiang University of Science and Technology, this paper analyzes the methods of improving high-quality employment through Second Classroom by questionnaires. It constructs a high-quality employment index using the second class index, ability index, and employment index from the principal component analysis and structural equations to provide empirical evidence and exploration for the qualitative development of applicative undergraduate institutions. Finally, some suggestions for optimizing the activities of the second classroom have been put forward.